2013
DOI: 10.1027/0227-5910/a000173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Negative Life Events and Suicidal Behavior

Abstract: Suicidal behavior associated with the experience of negative life events is not inevitable. Therapeutically bolstering competence, autonomy, and relatedness may be an important suicide prevention strategy for individuals experiencing life stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 51 publications
(72 reference statements)
7
26
0
1
Order By: Relevance
“…Consistent with past research, we expected to find NLE to be positively associated with both depressive symptoms and suicidal behaviors (e.g., Bonner & Rich, ; Rowe et al., ). Also, as a multifaceted psychological construct (Muris & Petrocchi, in press; Neff, , ), we expected positive facets of self‐compassion (viz., self‐kindness, common humanity, and mindfulness) to be negatively associated with both indices of suicidal risk.…”
Section: Purpose Of the Present Studysupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with past research, we expected to find NLE to be positively associated with both depressive symptoms and suicidal behaviors (e.g., Bonner & Rich, ; Rowe et al., ). Also, as a multifaceted psychological construct (Muris & Petrocchi, in press; Neff, , ), we expected positive facets of self‐compassion (viz., self‐kindness, common humanity, and mindfulness) to be negatively associated with both indices of suicidal risk.…”
Section: Purpose Of the Present Studysupporting
confidence: 84%
“…Consistent with this view, findings from numerous studies over the past four decades have shown that accumulated negative life events (NLE) is one of the most reliable correlates of greater suicidal risk in college students (e.g., Bonner & Rich, ; Chang et al., ; Dixon, Heppner, & Anderson, ; Heisel, Flett, & Hewitt, ). For example, in a sample of 439 college students, Rowe, Walker, Britton, and Hirsch () found that NLE was positively associated with both depressive symptoms and suicidal behaviors. Yet despite these consistent and convergent findings, what remains unclear is what might account for the positive association between the experience of NLE and suicidal risk in college students.…”
mentioning
confidence: 99%
“…A survey conducted by Reyes-Rodríguez et al (2013) found that negative life events increased the prevalence of depression symptoms and its severity among freshmen college students, which were regarded as one of important emotional maladjustment during school life. In addition, there is much evidence showing that negative life events could lead to suicidal behavior and other adverse outcomes across campus life (Rowe et al, 2013;Eisenberg et al, 2007). Consequently, finding ways to weaken the adverse effects of negative life events on school adjustment has become a major concern of researchers and educators.…”
Section: Introductionmentioning
confidence: 99%
“…There are substantial data about the influence of the occurrence of such events on further development and recurrence of mental health disorders. Aside from the onset of post-traumatic stress disorders, NLEs may influence the course of depression [2,3], anxiety [4,5], suicidal behavior [6] and cognitive performance [7]. …”
Section: Introductionmentioning
confidence: 99%